Rat lung response to ozone and fine particulate matter (PM2.5) exposures. Issue 3 (18th October 2013) - Wang, Guanghe; Zhao, Jinzhuo; Jiang, Rongfang; Song, Weimin
ABSTRACT Exposure to different ambient pollutants maybe more toxic to lung than exposure to a single pollutant. In this study, we discussed the inflammation and oxidative stress responses of rat lung caused by ozone and PM2.5 versus that of rats exposed to saline, ozone, or single PM2.5. Wistar rats inhaled 0.8 ppm ozone or air for 4 h and then placed in air for 3 h following intratracheal instillation with 0, 0.2 (low dose), 0.8 (medium dose), 3.2 (high dose) mg/rat PM2.5 dissolved in sterile saline (0.25 mL/rat), repeated twice per week for 3 weeks, the cumulative doses of PM2.5 in animals were 1.2, 4.8, and 19.2 mg. Rats were sacrificed 24 h after the last (sixth) exposure. The collected bronchoalveolar lavage fluid (BALF) was analyzed for inflammatory cells and cytokines. Lung tissues were processed for light microscopic and transmission electron microscopic (TEM) examinations. Results showed that total cell number in BALF of PM2.5‐exposed groups were higher than control (p < 0.05). PM2.5 instillation caused dose‐trend increase in tumor necrosis factor alpha (TNF‐α), interleukin‐6, lactate dehydrogenase, and total protein of BALF. Exposure to ozone alone only caused TNF‐α significant change in above‐mentioned indicators of lung injury. On the other hand, ozone could enhance PM2.5‐induced inflammatory changes and pathological characters in rat lungs. SOD and GSH‐Px activities in lung were reduced in PM2.5‐exposed rats with and without prior ozone exposure compared to control. To determine whether the PM2.5 and ozone affect endothelium system, iNOS, eNOS, and ICAM‐1 mRNA levels in lung were analyzed by real‐time PCR. These data demonstrated that inflammation and oxidative stress were involved in toxicology mechanisms of PM2.5 in rat lung and ozone potentiated these effects induced by PM2.5. These results have implications for understanding the pulmonary effects induced by ozone and PM2.5. © 2013 Wiley Periodicals, Inc. Environ Toxicol 30: 343–356, 2015.